Design and development of a direct methanol fuel cell for telecommunications - Joubert, Hardus (My University, 2013)
The demand for higher efficiency and cleaner power sources increases daily. The Direct Methanol Fuel Cells (DMFC) is one of those power sources that produces reliable electrical energy at high efficiencies and very low pollution levels. Remote telecommunication sites need power sources that can deliver reliable power. This dissertation informs the reader about the working principles of the DMFC and the materials it consists of. A good amount of theoretical background is also given on the DMFC, especially on the Membrane Electrode Assembly (MEA). Different membranes as well as their properties are discussed. Results from other researchers on DMFCs are also captured. A DMFC stack including a test rig, was built. The DMFC stack consisted of five single DMFC cells. Each cell contained an MEA, Gas Diffusion Layers (GDLS), highly corrosive resistant metal support grids, bipolar flow field plates and end plates. The DMFC stack was operated and tested in a test rig. The test rig held the air blower which supplied the cathode with the required oxidant (air), and the methanol solution tank plus its liquid pump. The liquid pump circulated the methanol solution through the anode side of the stack. It was observed that the DMFC is very susceptible to corrosion, especially if the methanol solution becomes conductive owing to solubility of C02 in it. Methanol itself is a corrosive substance. However the results obtained from the experiments clearly indicate that the DMFC can be implemented as an electrical power source for telecommunications.
Keywords: Power sources; Direct methanol fuel cell; Membrane Electrode Assembly; Power sources; Telecommunications; 621.38232; Direct methanol fuel cells; Telecommunication--Power supply.; Fuel cells